EVALUASI PROGRAM PENDIDIKAN KARAKTER PADA PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DI SMK NEGERI 2 PEKANBARU - Ratnasari, Desi; Azhar, Fadly; Hadriana, Hadriana (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2024)
The main objective of this study is to provide a detailed and in-depth description of the results obtained after the implementation of the character education program in the Pancasila Student Profile Strengthening Project at SMK Negeri 2 Pekanbaru. The study uses the CIPP model, which considers the aspects of Context, Input, Process and Product to comprehensively evaluate the program in question. This evaluation is a qualitative approach through a descriptive case study. The data needed for this assessment were collected through various methods such as interviews, field observations and analysis of related documents. The data analysis techniques used are data reduction, data presentation and conclusion. Data sources come from the principal, vice principal in charge of curriculum, vice principal in charge of student affairs, school treasurer, head of administrative staff, the Pancasila Student Profile Strengthening Project coordination team, teachers of the Pancasila Student Profile Strengthening Project, parents of students and students. The results of the study indicate that the character education program in the Pancasila Student Profile Strengthening Project has been implemented well by SMK Negeri 2 Pekanbaru. At the context stage, the average achievement level is 93% with a good category; at the input stage, it is 82.18% with a good category; at the process stage, it is 85% with a good category; and at the results stage, it is 75% in the pretty good category. The characteristics that are strengthened in the implementation of the character education program in the Pancasila Student Profile Strengthening Project, in general, are strengthening respect between fellow students and teachers and being able to take responsibility for their role as students at SMK Negeri 2 Pekanbaru.